Desenvolvimento, otimização e aceitabilidade de bebida de café com extrato hidrossolúvel da amêndoa de castanha de caju - Xerez, Ana Caroline Pinheiro (2012)
Coffee is a drink very much appreciated and consumed worldwide, especially also for its economic relevance that generates income and employability. In Brazil, the cultivation and processing of coffee are made predominantly in the Southeast. There are many productive areas in the state of Ceará who are idle due to lack of stimulation of producers and government incentive. Nevertheless, there are still some producers in the Massif Baturité, Ceará, Brazil to maintain its production cooperatives. Thus, this study aimed to develop and optimize a coffee beverage using coffee beans 100% Arabica, produced in Baturité Massif, added a water soluble extract of almond cashew (EHACC), in order to diversify the beverage market and add value to raw materials produced in Ceará. Initially, there were consumer profile analysis and sensory tests with a coffee drink made with grain produced in Ceará, in order to select the raw material of this study. From an experimental design, developed 12 formulations coffee drink with added EHACC. In the optimization study the beverage was considered factors quantity of sugar (g), and proportion of coffee (%) by developing an experimental compound central provided the application of Response Surface Methodology (RSM). This methodology was applied to the physico-chemical color, pH, ºBrix and viscosity and sensory variables overall impression, aroma, color, flavor, bitterness and body. For all variables were analyzed descriptively by frequency table and graphical analysis. According to the data of the consumer profile, the brewed coffee and milk added was preferred over other coffee beverages and more than 50% of consumers who responded buy a coffee beverage ready for consumption. A drink made with coffee beans of the Massif Baturité was classified as hard through the "cup test". The constraint limits established coffee and sugar defined in planning levels that led to the optimal points of the physico-chemical color (L *, b *) variables, pH and sensory overall impression, color and aroma of the coffee beverage of added EHACC. All variables evaluated showed good sensory acceptance in the 12 formulations tested.